Analysis of the influence of reinforcements on the microstructure and mechanical characterization of the Al-Flyash composites - Milind K. Wasekar; Mohan P. Khond (Fracture and Structural Integrity)
The aim of this work is to investigate the influence of the addition of silicon carbide and molybdenum disulfide on the microstructure and the tensile strength of the Al-Flyash hybrid composites prepared using the stir casting technique. The composite with aluminum 6061 alloy as the matrix and flyash as the reinforcement, with different weight fractions, is investigated to study its microstructure and the tensile strength. The same has been compared with the hybrid composites with Aluminum-Flyash/SiC and Aluminum-Flyash/MoS2 for different weight fractions of the reinforcements. The tensile tests were conducted as per ASTM standard testing procedures at room temperature. From the results it is identified that tensile strength of the Al6061-Flyash composite is lesser than the Al6061-Flyash/SiC and Al6061-Flyash/MoS2 hybrid composites. It is also observed that increment in the composition of the SiC and MoS2 causes the increment in the tensile strength of the hybrid composite. This increment in the tensile strength is due to good interface bonding and uniform distribution of the reinforcements in the composite.